Lignin–Chitosan Nanocarriers for the Delivery of Bioactive Natural Products against Wood-Decay Phytopathogens - Eva Sánchez-Hernández; Natalia Langa-Lomba; Vicente González-García; José Casanova-Gascón; Jesús Martín-Gil; Alberto Santiago-Aliste; Sergio Torres-Sánchez; Pablo Martín-Ramos (Agronomy, 2022)
The use of nanocarriers (NCs), i.e., nanomaterials capable of encapsulating drugs and releasing them selectively, is an emerging field in agriculture. In this study, the synthesis, characterization, and in vitro and in vivo testing of biodegradable NCs loaded with natural bioactive products was investigated for the control of certain phytopathogens responsible for wood degradation. In particular, NCs based on methacrylated lignin and chitosan oligomers, loaded with extracts from Rubia tinctorum, Silybum marianum, Equisetum arvense, and Urtica dioica, were first assayed in vitro against Neofusicoccum parvum, an aggressive fungus that causes cankers and diebacks in numerous woody hosts around the world. The in vitro antimicrobial activity of the most effective treatment was further explored against another fungal pathogen and two bacteria related to trunk diseases: Diplodia seriata, Xylophilus ampelinus, and Pseudomonas syringae pv. syringae, respectively. Subsequently, it was evaluated in field conditions, in which it was applied by endotherapy for the control of grapevine trunk diseases. In the in vitro mycelial growth inhibition tests, the NCs loaded with R. tinctorum resulted in EC90 concentrations of 65.8 and 91.0 μg·mL−1 against N. parvum and D. seriata, respectively. Concerning their antibacterial activity, a minimum inhibitory concentration of 37.5 μg·mL−1 was obtained for this treatment against both phytopathogens. Upon application via endotherapy on 20-year-old grapevines with clear esca and Botryosphaeria decay symptoms, no phytotoxicity effects were observed (according to SPAD and chlorophyll fluorescence measurements) and the sugar content of the grape juice was not affected either. Nonetheless, the treatment led to a noticeable decrease in foliar symptoms as well as a higher yield in the treated arms as compared to the control arms (3177 vs. 1932 g/arm), suggestive of high efficacy. Given the advantages in terms of controlled release and antimicrobial product savings, these biodegradable NCs loaded with natural extracts may deserve further research in large-scale field tests.